PERAN HUMAS DALAM MENINGKATKAN PROMOSI DAN CITRA DI SEKOLAH MADRASAH ALIYAH SWASTA PERSATUAN AMAL BAKTI 2 HELVETIA - Intan Fadillah; Nursapia Harahap; Rina Devianty (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2022)
The purpose of this research is to find out how the role of humans in increasing promotion and image in madrasas, whether it has been going well or whether the role of humans in schools has not gone well. Then to find out what obstacles humans experience and how to overcome these obstacles. This study uses a qualitative method. The informants used were the head of the madrasa, deputy head of the madrasa and public relations WKM 3 by means of purposive sampling. Data collection techniques used are interviews, observation and documentation. The results showed that madrasas had carried out their public relations role well, but there were several obstacles in the madrasa activity program so that public relations had difficulty promoting madrasa activities due to the conditions of the Covid-19 pandemic which required schools to be closed and teaching and teaching activities. learning activities are virtualized using the application that has been provided. Even though there are obstacles experienced by humans, they are able to overcome these obstacles by continuing to carry out these activities virtually even though not all annual activities are carried out.